Association of respiratory morbidity with duration of work among puffed rice workers in Davanagere city, Karnataka, India - G., Muhammed Muntazeem; Dsouza, Madonna J.; B. A., Varadaraja Rao; Patil, Basanth Kumar; Kengal, Prakash (International Journal Of Community Medicine And Public Health, 2020)
Background: Occupational respiratory disease can be defined as an acute or chronic disorder that arises from the inhalation of air-borne agents in the work place. Puffed rice is a famous food item in Karnataka, which is produced in a cluster of small units. Industrial dust inhalation over a long period of time leads to proliferative and fibrotic changes in the lungs. Methods: A cross sectional study was conducted among puffed rice workers in Bashanagar, urban field practice area of SSIMS and RC, Davanagere. From January 2017 to December 2017. The study population included 550 puffed rice unit workers. Data was collected using structured interview along with anthropometric measurements. Spirometry was done by using RMS (Helio’s) Spirometer. Results: In this study significant association was found between respiratory morbidity and duration of work. The risk of obstructive lung disease was 0.18 (0.03-1.40) times less among workers who worked for <5 years compared to workers who worked for more than 20 years. The risk of restrictive lung disease was 0.35 (CI 0.16-0.77) times lower among workers who worked for <5 years compared to the workers who worked for > 20 years and the association was statistically significant with p value of 0.010. Conclusions: The risk of respiratory morbidity was significantly associated with increase in the duration of work.